Pemanfaatan Teknologi Desalinasi Filtrasi Sederhana Untuk Memenuhi Kebutuhan Air Tawar - Novitasari, Zirma; Andini, Andini; Eddy, Syaiful (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The clean water crisis in coastal areas is a major challenge due to limited access to freshwater sources. The use of simple filtration desalination technology is a potential solution to overcome this problem. This study aims to analyze how to overcome the clean water crisis in coastal areas by reviewing effective simple filtration desalination technology. The review method used in writing this paper is a literature review of various articles related to simple desalination technology, which involves the use of natural materials such as sand, activated charcoal, and coconut fiber. The results of the study show that this technology offers a more affordable and environmentally friendly alternative compared to more complex and expensive desalination technologies. However, there are still challenges in terms of water efficiency and quality that need to be tested regularly. In conclusion, simple filtration desalination has great potential to be implemented in coastal areas that lack clean water, provided that there is further development and improvement in its application.